Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Tungstophosphoric acid supported over zirconia in mesoporous channels of MCM-41 as catalyst in veratrole acetylation - Sawant, Dhanashri P.; Vinu, A.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 were synthesized and tested for their catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5-50 wt.%) on 22.4 wt.%ZrO2/MCM-41 and 15 wt.%TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. The physico-chemical characterization of the supported catalysts was done by powder X-ray diffraction (XRD), surface area measurement (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed-infrared (FT-IR) spectroscopy, UV-vis diffuse reflectance spectra, Temperature programmed desorption (TPD) of ammonia, FT-IR pyridine adsorption and (31) P cross polarization-magic angle spinning (CP-MAS) NMR spectroscopy. The mesoporous silica supports play an important role in stabilizing catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/MCM-41 calcined at 1123 K was found to have highest acidity and at least four times more active than neat 15 wt.%TPA/ZrO2 in veratrole acetylation to acetoveratrone by acetic anhydride. Reaction conditions were evaluated with 15 wt.%TPA/22.4 wt:%ZrO2/MCM-41 calcined at 1123 K to get higher conversion of acetic anhydride to acetoveratrone. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) TPA into the medium under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetoveratrone; acetylation; MCM-41; TPA/ZrO2; veratrole

Heteropoly acid encapsulated SBA-15/TiO(2) nanocomposites and their unusual performance in acid-catalysed organic transformations - Sawant, Dhanashri P.; Justus, Josena; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Srinivasu, Pavuluri; Velmathi, Sivan; Halligudi, Shivappa B.; Vinu, Ajayan (Chemistry-A European Journal, 2008)
The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungsto-phosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calcination temperature. TPA and TiO(2) loadings of 15 and 22.4 wt %, respectively, and a calcination temperature of 1123 K have proved to be optimal for obtaining mesoporous nanocomposite materials with the highest acidity. Moreover, the activities of these catalysts in promoting hydroamination as well as Mannich and Claisen rearrangement reactions have been extensively investigated. The results show that the amount of TPA has a great influence on the activity of the nanocomposites in all of the reactions studied. The effects of other reaction parameters, such as temperature and reaction time, on the conversion and product selectivity have also been studied in detail. A kinetic analysis of the formation of the products under various reaction conditions is presented. It has been found that the activity of the nanocomposite composed of 15 wt % TPA deposited on 22.4 wt of TiO(2) on SBA-15 in promoting the studied reaction is remarkably higher than the catalytic activities shown by pure TPA, TiO(2)-loaded SBA-15, or TPA-loaded SBA-15. The results obtained have indicated that the acidity and the structural control of the nanocomposite materials are highly critical for obtaining excellent catalytic activity, and the presented highly acidic nanocomposites are considered to show great potential for use as catalysts in promoting many acid-catalysed organic transformations.
Keywords: Bronsted acids; mesoporous materials; nanoreactors; nanotechnology; supported catalysts

Novel three dimensional cubic Fm3m mesoporous aluminosilicates with tailored cage type pore structure and high aluminum content - Srinivasu, Pavuluri; Alam, Sher; Balasubramanian, Veerappan V.; Velmathi, Sivan; Sawant, Dhanashri P.; Boehlmann, Winfred; Mirajkar, Subhash P.; Ariga, Katsuhiko; Halligudi, Shivappa B.; Vinu, Ajayan (Advanced Functional Materials, 2008)
Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AIKIT-5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N, adsorption, HRTEM, HRSEM, EDS, elemental mapping, Al-27 MAS NMR, and NH3-TPD. We also demonstrate that the nature, and the amount of Al incorporation in the silica framework can easily be controlled by simply varying the n(H2O)/n(HCl) and the n(Si)/n(Al), ratios, and the Al sources in the synthesis gel. Among the Al sources examined, the Al isopropoxide (AiPr) is superior over other Al sources. Al-27 MAS NMR results reveal that the amount of tetrahedral Al in the framework can be controlled by simply adjusting the nSi/nAl ratio in the synthesis gel, which increases with increasing the Al incorporation. One of the interesting findings in the work is the increase of the specific surface area, specific pore volume and the pore diameter of AIKIT-5 with increasing the Al incorporation in the silica framework (up to n(Si)/n(Al), ratio of 10) while retaining the well-ordered three dimensional cage type porous structure, and the mechanism for the unusual behavior has been discussed in detail. Finally, the acidity and the catalytic activity in the acetylation of veratrole of the AIKIT-5 catalysts have been studied and the results have been compared with the several zeolites catalysts. Among the catalysts examined, AIKIT-5(10) is found to be superior over the zeolites catalysts such as mordenite, zeolite H-Y, zeolite H-beta, and ZSM-5.

Synthesis of biodiesel over zirconia-supported isopoly and heteropoly tungstate catalysts - Sunita, G.; Devassy, Biju M.; Vinu, Ajayan; Sawant, Dhanashri P.; Balasubramanian, Veerappan V.; Halligudi, Shivappa B. (Catalysis Communications, 2008)
The liquid-phase synthesis of biodiesel by transesterification of sunflower oil with methanol is carried out by using zirconia-supported isopoly and heteropoly tungstates (HPAs) as catalysts. The isopoly and heteropoly tungstate catalysts were prepared by suspending zirconium oxyhydroxide in water/methanol solution of ammonium metatungstate/silicotungstic acid, phosphotungstic acid (WO3/HPA loading, 15%,,) followed by drying and calcination at 750 degrees C. The catalysts were characterized by XRD, Raman spectroscopy, IR spectroscopy, NH3-TPD and FTIR pyridine adsorption spectroscopy. XRD results indicate that the presence of isopoly and heteropoly tungstates stabilizes ZrO2 in tetragonal phase. Raman and IR spectra of the catalysts show that tungstate species exist as zirconia-anchored octahedral mono-oxotungstate. The acidity measurements by NH3-TPD and FTIR pyridine adsorption spectroscopy show that zirconia-supported phosphotungstate has the highest total acidity and zirconia-supported isopoly tungstate has the highest Bronsted acidity. The zirconia-supported isopoly tungstate shows superior catalytic performance compared to zirconia-supported heteropoly tungstate catalysts. Under the reaction conditions of 200 degrees C and methanol/oil molar ratio 15, 15% WO3/ZrO2 calcined at 750 degrees C gave 97% conversion of oil. This catalyst also efficiently catalyzes methanolysis of other vegetable oils like mustard oil and sesame oil. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; phosphotungstic acids; Silicotungstic acid; transesterification; tungsten oxide; Zirconia

Direct synthesis of mesoporous siliceous phosphotungstic acid and its superior catalytic activity on the cyclohexylation of phenol - Ilbeygi, Hamid; Sawant, Dhanashri P.; Ruban, Sujanya M.; Reshma, Kokane S.; Umbarkar, Shubhangi B.; Halligudi, Shivappa B.; Vinu, Ajayan (Journal of Physical Chemistry C, 2021)
The synthesis of highly active and reusable mesoporous siliceous phosphotungstic acid materials (mPTA-Si) which are prepared through a simple self-assembly between phosphotungstic acid (PTA), the polymeric surfactant, and the silica precursor assisted by KCl for cyclohexylation of phenol is reported. The surface area and the acidity of these materials are tuned with a simple adjustment of PTA in the silica framework. The prepared samples exhibit mesoporous structure with a high surface area, but the structure is collapsed when the loading of PTA is high. It is established that the Keggin structure of PTA is retained on the final mPTA-Si. mPTA-Si with different loadings of PTA are employed as the catalysts for the cyclohexylation of phenol under liquid phase conditions. Among the catalysts studied, 10.0-mPTA-8.3Si calcined at 350 degrees C is found to be highly active, selective, and recyclable and offers 100% conversion of phenol with the highest selectivity for p-cyclohexylphenol (96.8%).